Characteristics of Yogurt Ice Cream Fortified with Red Dragon Fruit Puree as Anti-Obesity Functional Food - Susanti, Siti; Legowo, Anang M.; Mulyani , Sri; Pratama, Yoga (Jurnal Gizi dan Pangan, 2022)
This study aimed to determine the effect of Red Dragon Fruit Puree (RDP) added to yogurt ice cream on its sensory, physical and chemical characteristics as well as its anti-obesity effect on mice fed with high-fat diet. To obtain the optimal addition level, RDP was added to the yogurt-based ice cream dough in various proportions: 0 (control), 10, 20, 30, and 40%. The sensory evaluation signifies that 30% RDP addition results in the best yogurt ice cream because it produces favorable flavor, attractive color (purplish pink), and the most preferable taste for the panelist. Data on physical and chemical characteristics showed that RDP yogurt ice cream has lower overrun, total solid, fat, carbohydrate, and calorie content than non-RDP yogurt ice cream (p<0.05). The animal test identified that consumption of RDP yogurt ice cream for 14 days could reduce the mice’s (a xenograft model) body weight under normal and high-fat diet conditions (p<0.05). Thus, RDP yogurt ice cream with specific physical and chemical characteristics potentially results in anti-obesity effects in pre-clinic setting. RDP yogurt ice cream merits further studies, especially for clinical test, before the commercialization stage.